PERANCANGAN APLIKASI SKRINING GUNA EFEKTIVITAS PENGISIAN KUISONER SKRINING DI PUSKESMAS PABUARAN SUBANG - Yuyun Yunengsih; Isty Youandinie; Rini Suwartika Kusumadiarti (INFOKOM (Informatika & Komputer), 2025)
This study aims to develop a screening questionnaire application to improve the effectiveness, efficiency, and accuracy of the questionnaire filling process at Pabuaran Subang Public Health Center. The development method used is the Rational Unified Process (RUP) consisting of the inception, elaboration, construction, and transition phases. The main problem is that the process is still manual, requiring a long time, prone to input errors, and difficult for data processing. The results show that the developed application accelerates filling, minimizes recording errors, and facilitates health workers in accessing and analyzing screening data. This application is expected to be further developed into an integrated system with real-time data analysis to enhance the quality of public health services